THE EFFECTIVENESS OF TEACHING SPEAKING BY USING ROLE PLAY METHOD TO THE SECOND GRADE STUDENTS OF SMPN 1 SEMEN KEDIRI - Fadhillah, Fadhillah (LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
The purpose of this research is to find out (1) the students’ speaking skill before being taught by usingrole play method, (2) the students’ speaking skill after being taught by using role play method, (3) the significant difference of students’ speaking skill before and after being taught by using role play method, and (4) the effectiveness of teaching speaking by using role play method to the second grade students of SMPN 1 Semen Kediri. This research used quantitative experimental design, because the result is related to the number that is computed quantitatively. The subject of this research is the second grade students of SMPN 1 Semen Kediri. The number of students is 36 . There were 3 steps in doing the research, namely pre-test, treatment, and post-test. The research was done 10 days. The result of this research is (1) The students’ speaking skill before being taught by using role play method to the second grade students at SMPN 1 Semen was in fair category with the mean 49.22. ( 2) The students’ speaking skill after being taught by using role play method to the second grade students at SMPN 1 Semen was in good category with the mean 76.22.(3)There is significant different of students’ speaking skill before and after using role-play method to the second grade students at SMPN 1 Semen. It was proved by the result of t-test which was higher than t-table at 5% and 1% which is known as 2.03<29.327>2.72 . (4) Teaching speaking by using role play method to the second grade students at SMPN 1 Semen is effective.